Effect of varicoceles on spermatogenesis. (January 2022) - Kang, Caroline; Punjani, Nahid; Lee, Richard K.; Li, Philip S.; Goldstein, Marc
Abstract: Varicoceles are dilated veins within the spermatic cord and a relatively common occurrence in men. Fortunately, the large majority of men are asymptomatic, however, a proportion of men with varicoceles can suffer from infertility and testosterone deficiency. Sperm and testosterone are produced within the testis, and any alteration to the testicular environment can negatively affect the cells responsible for these processes. The negative impact of varicoceles on testicular function occurs mainly due to increased oxidative stress within the testicular parenchyma which is thought to be caused by scrotal hyperthermia, testicular hypoxia, and blood-testis barrier disruption. Management of varicoceles involves ligation or percutaneous embolization of the dilated veins. Repair of varicoceles can improve semen parameters and fertility, along with serum testosterone concentration. In this review, we discuss the pathophysiology of varicoceles, their impact on testicular function, and management. Highlights: Varicoceles are common in men. Varicoceles can negatively affect spermatogenesis and testosterone production. Oxidative stress from varicoceles occurs due to hyperthermia, tissue hypoxia, and blood-testis barrier dysfunction. Indications for varicocele include infertility, testosterone deficiency, pain, and cosmesis. Varicocele repair can improve fertility and raise serum testosterone levels.